Probing Acidic and Defective Sites in Sulfated UiO-66 and ZrO2 via Adsorptive FTIR Spectroscopy - Vera V. Butova; Olga A. Burachevskaia; Nikola L. Drenchev; Andrei A. Tereshchenko; Konstantin I. Hadjiivanov (Nanomaterials)
Sulfation is a common strategy to enhance the acidity and modify the adsorption properties of metal–organic frameworks (MOFs), yet its impact on the coordination and accessibility of active sites remains unclear. In this study, we investigate two structurally related systems—sulfated UiO-66 (UiO-66-SO4) and sulfated tetragonal zirconia (S-ZrO2)—by FTIR spectroscopy with probe molecules. Isotope exchange experiments on S-ZrO2 reveal that dehydration above 250 °C induces tridentate SO4 coordination, while hydration leads to a reversible transition to a bidentate coordination mode. In UiO-66-SO4, sulfates are coordinated in a bidentate fashion to Zr6O6 clusters, significantly affecting the accessibility of Zr sites in defective pores. This coordination prevents CO adsorption but allows acetonitrile adsorption even after room temperature activation. Unlike S-ZrO2, due to its lower thermal stability, UiO-66-SO4 cannot be evacuated at high temperatures and dehydration at 250 °C does not induce tridentate coordination. The presence of H-bonded hydroxyls in UiO-66-SO4 after activation at 250 °C supports this coordination model, indicating the formation of OH-coordinated Zr sites that are inaccessible to CO but interact with stronger bases like acetonitrile. Overall, this study provides new insights into the coordination chemistry of sulfated UiO-66 and highlights that sulfation can tune acidity and adsorption in MOFs for potential catalytic and adsorption applications.